Preclinical Evaluation of Polymeric Nanocomposite Containing Pregabalin for Sustained Release as Potential Therapy for Neuropathic Pain - Rafaela Figueiredo Rodrigues (MDPI AG, 2021)
This study offers a novel oral pregabalin (PG)-loaded drug delivery system based on chitosan and hypromellose phthalate-based polymeric nanocomposite in order to treat neuropathic pain (PG-PN). PG-PN has a particle size of 432 ± 20 nm, a polydispersity index of 0.238 ± 0.001, a zeta potential of +19.0 ± 0.9 mV, a pH of 5.7 ± 0.06, and a spherical shape. Thermal and infrared spectroscopy confirmed nanocomposite generation. PG-PN pharmacokinetics was studied after a single oral dose in male Wistar rats. PG-PN showed greater distribution and clearance than free PG. The antinociceptive effect of PG-PN in neuropathic pain rats was tested by using the chronic constriction injury model. The parameter investigated was the mechanical nociceptive threshold measured by the von Frey filaments test; PG-PN showed a longer antinociceptive effect than free PG. The rota-rod and barbiturate sleep induction procedures were used to determine adverse effects; the criteria included motor deficit and sedative effects. PG-PN and free PG had plenty of motors. PG-PN exhibited a less sedative effect than free PG. By prolonging the antinociceptive effect and decreasing the unfavorable effects, polymeric nanocomposites with pregabalin have shown promise in treating neuropathic pain.